Anomeric sugar boronic acid analogues as potential agents for boron neutron capture therapy - Imperio, Daniela; Del Grosso, Erika; Fallarini, Silvia; Lombardi, Grazia; Panza, Luigi (Beilstein Journal of Organic Chemistry, 2019)
After the development of accelerators as neutron source, the access to new suitable agents for boron neutron capture therapy (BNCT) became a major need. Among many others, sugar boronic acids have recently attracted attention as boron carriers. Herein we report the synthesis and preliminary biological studies of two new sugar analogues containing a boronic acid at the anomeric position. The analogues were obtained by hydroboration of proper open-chain terminal alkenes that, after quenching with water, spontaneously afforded cyclic boronic acids with hemiacetal-like structures.
Keywords: antitumor agents; boron neutron capture therapy; boronic acid; hydroboration; sugar analogue